Examining the Commonalities and Differences Between Gamblification and Gamification: A Theoretical Perspective - Macey, Joseph (Taylor & Francis Inc., 2025)
Gamification has arguably emerged as the most dominant of persuasive technologies, giving rise to a multidisciplinary field and diverse associated industries. As the field has grown, so too has the need for further resolution, nuance, and conceptual acuity; it is important to be able to distinguish different facets once the use of umbrella terminology becomes insufficient. One notable area of interest is gamblification, the study of which is not yet as well-developed; while gamblification is often conceptualized as an extension of gamification, recent research has found it to be an effective means of engaging users in alternative ways. This article examines points of similarity and difference between gamblification and gamification, with the intention to highlight the scope of gamblification as a means to promote specific user behavior and, furthermore, to provide a clear theoretical basis for the ongoing investigation into this phenomenon. The most significant point of difference is that while successful gamification primarily utilizes intrinsic motivations to effect meaningful change, gamblification does so predominantly through leveraging extrinsic motivations. Consequently, gamification and gamblification are used to achieve different aims and are suited to different contexts. Finally, a future research agenda for developing the study of gamblification is presented.